PENGARUH UMUR PEMOTONGAN TERHADAP PRODUKSI BIOMASSA DAN KANDUNGAN NUTRIEN RUMPUT CIPELANG (Pennisetum purpureum cv. Taiwan) PADA PERTUMBUHAN KEMBALI KETUJUH (The Effect of Cutting Age on Biomass Production and Nutrient Content of Cipelang Grass.....) - Kasi, Aloysius Edwin R.; kleden, markus miten; Lestari, Gusti Ayu Y. (Universitas Nusa Cendana, 2025)
This study aimed to determine the effect of cutting age on biomass production and nutritional content of Cipelang grass (Pennisetum purpureum cv. Taiwan) in the seventh regrowth. The research was conducted in Naibonat Village RT. 22 RW. 08 East Kupang District Kupang Regency East Nusa Tenggara from April to August 2024. The tools used in this study included a measuring tape, a SF-400 digital scale with a capacity of 10 kg, scissors, and calipers. The materials used were Cipelang green grass and chemicals for laboratory analysis. The method used in this research is an experimental method (experiment) by using a completely randomized design (CRD) consisting of 3 treatments 4 replications. The treatments are: UP30 = 30-day cutting, UP60 = 60-day cutting, UP90 = 90-day cutting. The results showed that the highest fresh biomass production at 90 days cutting age was 76.92 tons/ha, the highest dry matter content at 90 days cutting age was 21.93%, the highest organic matter at 90 days cutting age was 85.28%, the highest crude fiber at 90 days cutting age was 25.31%, while the highest crude protein content at 30 days cutting age treatment was 12.18%. The results of statistical analysis showed that the cutting age treatment had a very significant effect (P <0.01) on fresh biomass production, dry matter content, organic matter, crude protein and crude fiber of Cipelang grass. It was concluded that biomass production, dry matter content, organic matter, crude fiber, were highly dependent on cutting age and increased with increasing cutting age. Crude protein content showed the opposite fact, which decreased with increasing cutting age and the best cutting age at 90 days.